2010
DOI: 10.1155/2010/212696
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Positioning on Plain Levobupivacaine Spinal Anesthesia in Cesarean Section

Abstract: Background. The behaviour of isobaric levobupivacaine in relation to gravity when used in obstetric spinal anesthesia is unclear. Methods. 46 women with ASA physical status 1 undergoing cesarean section were randomly allocated to 2 groups. Spinal anesthesia with 12.5 mg levobupivacaine was performed in the sitting position in all women. Those in the first group were placed in the supine position immediately after the injection, while those in the second group were asked to remain seated for 2 minutes before as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…There is still a belief that plain local anesthetics give unpredictable blocks [8,9], but in our study, using a 10 mg dose of plain levobupivacaine, a predictable anesthesia was achieved and the success rate was high. Similar results were found by Gori et al [10] using isobaric levobupivacaine for Caesarean section. Hunt et al [11] reported that fentanyl given intrathecally in conjunction with 0.5% levobupivacaine improved the quality of intraoperative analgesia, prolonged the duration of postoperative analgesia and retarded the sensory anesthesia regression without delaying motor regression.…”
Section: Discussionsupporting
confidence: 89%
“…There is still a belief that plain local anesthetics give unpredictable blocks [8,9], but in our study, using a 10 mg dose of plain levobupivacaine, a predictable anesthesia was achieved and the success rate was high. Similar results were found by Gori et al [10] using isobaric levobupivacaine for Caesarean section. Hunt et al [11] reported that fentanyl given intrathecally in conjunction with 0.5% levobupivacaine improved the quality of intraoperative analgesia, prolonged the duration of postoperative analgesia and retarded the sensory anesthesia regression without delaying motor regression.…”
Section: Discussionsupporting
confidence: 89%
“…fluids. Thus group D patients were haemodynamically less stable compared to group S. In the study of Gupta et.al 17 . (2011) hypotention was more in the dexmedetomidine group than in fentanyl group but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 84%
“…Bouvet et al 21 reported that, when combined with opioids, ED 95 of intrathecal levobupivacaine is 12.9 mg for caesarean delivery. Gori et al 22 evaluated infl uence of positioning on 12.5 mg plain levobupivacaine spinal anesthesia in cesarean section. In our study, the same spinal doses according to the patient height was administered to all the patients to ensure a suffi cient level of anesthesia, especially in Group 1, and not to adversely infl uence the comfort of the patient during cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%